2017
DOI: 10.1007/s10924-017-1025-2
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Characterization of Environmentally Friendly Composites from Biobased Polyethylene and Natural Fillers from Thyme Herbs

Abstract: The main aim of this research work is to assess the potential of a distillery waste from thyme as multifunctional filler in natural fiber reinforced plastics (NFRP) with biobased polyethylene matrix. Several ethylene-based copolymers with different co-monomers (vinyl alcohol, methyl methacrylate, glycidyl methacrylate and acrylic acid) were used as compatibilizer agents to overcome the lack of compatibility between the highly hydrophobic matrix and the highly hydrophilic lignocellulosic filler. The effect of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
18
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 48 publications
8
18
0
3
Order By: Relevance
“…At higher temperatures, the free radicals formed led to sequential thermal degradation and breakdown of the main polyolefin chain [58]. Finally, all the film samples showed a similar residual mass of 0.2%-0.3%, indicating full thermal decomposition at 700 • C. In this sense, Montanes et al [59] observed a similar thermal degradation profile for this green polyolefin, which was based on a one-step weight loss that ranged between 390 and 508 • C. The addition of 0.3 and 0.8 phr of GA successfully induced an improvement in the bio-based HDPE film of approximately 27 and 35 • C in the T onset value, respectively, and suppressed the formation of the above-described free radicals. This thermal stability enhancement was relatively similar to that obtained above by DSC, as shown in previous Table 3, which is related to the intrinsic antioxidant activity of the natural polyphenol.…”
Section: Filmmentioning
confidence: 88%
“…At higher temperatures, the free radicals formed led to sequential thermal degradation and breakdown of the main polyolefin chain [58]. Finally, all the film samples showed a similar residual mass of 0.2%-0.3%, indicating full thermal decomposition at 700 • C. In this sense, Montanes et al [59] observed a similar thermal degradation profile for this green polyolefin, which was based on a one-step weight loss that ranged between 390 and 508 • C. The addition of 0.3 and 0.8 phr of GA successfully induced an improvement in the bio-based HDPE film of approximately 27 and 35 • C in the T onset value, respectively, and suppressed the formation of the above-described free radicals. This thermal stability enhancement was relatively similar to that obtained above by DSC, as shown in previous Table 3, which is related to the intrinsic antioxidant activity of the natural polyphenol.…”
Section: Filmmentioning
confidence: 88%
“…Polymers 2019, 11,1908 10 of 20 Figure 3. Variation of the melt flow index (MFI) and its percentage increase (Δ%) of polylactide (PLA) subjected to different reprocessing cycles.…”
Section: 2mentioning
confidence: 99%
“…Polymers 2019, 11,1908 11 of 20 Figure 4. A comparative plot of the differential scanning calorimetry (DSC) thermograms during second heating corresponding to the injection-molded polylactide (PLA) pieces subjected to different reprocessing cycles.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the hydrophilic nature of natural fibers, poly(ethylene-co-glycidil methacrylate) (PEGM) supplied by Sigma-Aldrich (Sigma-Aldrich Química, S.A., Madrid, Spain) was used as compatibilizer to increase polymer-filler interaction [16].…”
Section: Methodsmentioning
confidence: 99%